Organisasi Pembelajar Pada Pengusaha Batik di Jawa Tengah - Septina Dwi Retnandari; Fitri Suprapti (Jurnal Maritim Polimarin, 2017)
Research on the 'Learning Organization' will answer the question: What is the description of organizational learning 'in the batik business in Central Java? This study uses a type of analytical description research. The   population is all batik business in all cities in Central Java. The method to determine sample is purposive random sampling. It appointed batik entrepreneurs in the cities of Solo, Salatiga and Pekalongan as respondents. Determination of research locations is that they represented the development of batik in Central Java and was based on the specific problems of each city. Data collection methods are observation, interview and questionnaire. The method of data analysis is qualitative method. Learning organization consist of personal mastery, mental models, shared vision, team learning, systemic thinking. Learning organization will have advantages and disadvantages when it is applied by batik entrepreneurs in Central Java. From research findings, it can be concluded that learning organizations in Central Java can be expected to develop with a number of conditions. Learning organization will develop if it comes from business owners together with its aim to build efficient business processes and the need for innovation and creativity; and learning organization will increase if it is supported by the government and batik business associations together with its aim to increase regional income.